Life course and work ability among older adults: ELSI-Brazil - Camila Menezes Sabino de Castro; Maria Fernanda Lima-Costa; Cibele Comini César; Jorge Alexandre Barbosa Neves; Fabíola Bof de Andrade; Paulo Roberto Borges de Souza Junior; Rosana Ferreira Sampaio (Revista de Saúde Pública, 2018)
ABSTRACT OBJECTIVE To examine factors associated with perception of work ability in a nationally representative sample of Brazilians aged 50 years and over. METHODS We used data from 8,903 participants of the baseline survey of the Brazilian Longitudinal Study of Aging (ELSI-Brazil). The dependent variable was self-rated work ability (good or very good versus fair, poor, or very poor). Independent variables included factors that operate at the beginning, middle, and current stage of life. Multivariate analysis was based on prevalence ratios (PR) and 95% confidence intervals (95%CI) estimated by Poisson regression. RESULTS Good work ability was reported by 49% of \ participants (49.4% among men and 48.6% among women). Results of the multivariate analysis showed that, for both men and women, good work ability showed positive and statistically significant associations (p < 0.05) with good health up to 15 years of age (PR = 1.22 and 1.18 , respectively), educational level ≥ 8 years (PR = 1.19 and 1.21, respectively), and current good self-rated health (PR = 1.88 and 1.94, respectively). Negative associations were observed for current age (PR = 0.99 for each increase of one year among men and women), medical diagnosis of depression (PR = 0.70 for men and PR = 0.87 for women), and having one or more at least chronic diseases (PR = 0.88 for men and 0.91 for women). Only for men, positive associations for the age at which they started working (PR = 1.14 and 1.12 for 11–17 and ≥ 18 years, respectively) and living with a spouse (PR = 1.09) were found. CONCLUSIONS Work ability in older ages is built over the life course, particularly by the health conditions in childhood and adolescence, age at which men begin working, educational level, and health conditions in older ages. Policies aimed at increasing longevity in the labor market must take these factors into account.